Peran Kepuasan Kerja dalam Memediasi Hubungan antara Lingkungan Kerja dan Kompensasi terhadap Produktivitas - Riyadi, Sugeng; Indah Sari, Yuli; Hapsari, Vinandri; Teruna Bakti, Ilham (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the influence of work environment and compensation on employee productivity, with job satisfaction serving as a mediating variable among employees of Hari Hari Supermarket, Fatmawati branch. The research adopts a descriptive quantitative approach involving a sample of 100 employees. Data were collected through structured questionnaires and analyzed using the Smart Partial Least Squares (Smart PLS) method. The findings reveal that the work environment has a positive and significant effect on job satisfaction. Similarly, compensation exerts a positive and significant influence on job satisfaction. The results also indicate that the work environment has a positive impact on productivity, while compensation positively and significantly affects productivity as well. Furthermore, job satisfaction is found to have a positive and significant effect on employee productivity. The mediation analysis demonstrates that job satisfaction mediates the relationship between the work environment and productivity, as well as between compensation and productivity. These findings highlight that a conducive work environment and fair compensation system are essential to enhancing job satisfaction and, consequently, improving productivity among retail employees. The study contributes to human resource management literature by emphasizing the strategic role of job satisfaction as a key mediating factor linking workplace conditions and compensation to productivity outcomes. It also provides practical insights for retail managers to design effective human resource policies that foster employee engagement, satisfaction, and long-term performance